A Synthesis of Engel Curve Theory - Aitchison, J.; Brown, J. A. C. (Review of Economic Studies, 1954)
J. Aitchison, J. A. C. Brown; A Synthesis of Engel Curve Theory1, The Review of Economic Studies, Volume 22, Issue 1, 1 January 1954, Pages 35–46, https://